The Tulane accelerated physician training program (TAP-TP): A novel combination of scholarship and service. (4th March 2021) - Woodson, Michael J.; Morris, Cindy A.; Mullin, David A.; Maclaren, James M.; Rhines, Bradford W.; Nance, Agnieszka B.; Sachs, Benjamin; Kahn, Marc J.
Abstract: Introduction: In spite of a projected shortage of physicians in the USA, the relatively long time and duration of training and high expense, the education of U.S. physicians has changed little over the past 120 years. Methods: To address these issues, Tulane University developed a program, the Tulane accelerated physician training program (TAP-TP). This unique program allows selected Tulane undergraduate students to complete two years of undergraduate studies, followed by a mandatory year of public service, prior to four years of medical school. Results: Students almost exclusively major in Cell and Molecular Biology (CMB), and used credits earned in Medical School to complete the required hours for their Bachelor's degree. The program was judged to be successful based on its ability to attract, retain, and graduate students into medical residency programs. The shortened time frame needed to complete the undergraduate program is associated with significant cost savings for the students. Educational outcomes were not statistically different between TAP-TP and traditional students despite the accelerated curriculum. Conclusions: TAP-TP is a unique model to graduate physicians in an accelerated fashion at significant cost savings.